Habitat fragmentation and adaptation: a reciprocal replant-transplant experiment among 15 populations of Lychnis flos-cuculi - Bowman, Gillianne; Perret, Catherine; Hoehn, Sophie; Galeuchet, David J.; Fischer, Markus (The Journal of ecology, 2008)
1. Habitat fragmentation and variation in habitat quality can both affect plant performance, but their effects have rarely been studied in combination. We thus examined plant performance in response to differences in habitat quality for a species subject to habitat fragmentation, the common but declining perennial herb Lychnis flos-cuculi. 2. We reciprocally transplanted plants between 15 fen grasslands in north-east Switzerland and recorded plant performance for 4 years. 3. Variation between the 15 target sites was the most important factor and affected all measures of plant performance in all years. This demonstrates the importance of plastic responses to habitat quality for plant performance. 4. Plants from smaller populations produced fewer rosettes than plants from larger populations in the first year of the replant-transplant experiment. 5. Plant performance decreased with increasing ecological difference between grassland of origin and target grassland, indicating adaptation to ecological conditions. In contrast, plant performance was not influenced by microsatellite distance and hardly by geographic distance between grassland of origin and target grassland. 6. Plants originating from larger populations were better able to cope with larger ecological differences between transplantation site and site of origin. 7. Synthesis: In addition to the direct effects of target grasslands, both habitat fragmentation, through reduced population size, and adaptation to habitats of different quality, contributed to the performance of L. flos-cuculi. This underlines that habitat fragmentation also affects species that are still common. Moreover, it suggests that restoration projects involving L. flos-cuculi should use plant material from large populations living in habitats similar to the restoration site. Finally, our results bring into question whether plants in small habitat remnants will be able to cope with future environmental change.